Role of Non-coding RNAs on the Radiotherapy Sensitivity and Resistance of Head and Neck Cancer: From Basic Research to Clinical Application - Zhang, Xixia; Yang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Head and neck cancers (HNC) rank as the sixth common and the seventh leading cause of cancer-related death worldwide, with an estimated incidence of 600,000 cases and 40–50% mortality rate every year. Radiotherapy is a common local therapeutic modality for HNC mainly though the function of ionizing radiation, with approximately 60% of patients treated with radiotherapy or chemoradiotherapy. Although the radiotherapy is more advanced and widely used in clinical practice, the 5-year overall survival rates of locally advanced HNC are still less than 40%. HNC cells resistance to radiotherapy remains one of the major challenges to improve the overall survival in HNC patients. Noncoding RNAs (ncRNAs) are newly discovered functional small RNA molecules that are different from messenger RNAs which can be translated into a protein. Many previous studies have reported the dysregulation and function of ncRNAs in HNC. Importantly, researchers reported that several ncRNAs were also dysregulated in radiotherapy-sensitive or radiotherapy-resistant HNC tissues compared with the normal cancer tissues. They found that ectopically elevating or knocking down expression of some ncRNAs could significantly influence the response of HNC cancer cells to radiotherapy, indicating that ncRNAs could regulate the sensitivity of cancer cells to radiotherapy. The implying mechanism for ncRNAs in regulating radiotherapy sensitivity may be due to its roles on affecting DNA damage sensation, inducing cell cycle arrest, Regulating DNA damage repair, and modulation of cell apoptosis etc. Additionally, clinical studies reported that in situ ncRNA expression in HNC tissues may predict response of radiotherapy and circulating ncRNA from body liquid serves as minimally invasive therapy-responsive and prognostic biomarkers in HNC. In this review, we aimed to summarize the current function and mechanism of ncRNAs in regulating the sensitivity of HNC cancer cells to radiotherapy and comprehensively described the state of the art on the role of ncRNAs in the prognosis prediction, therapy monitoring and prediction of response to radiotherapy in HNC.